The re-enchantment of life, nature and the cosmos from transpersonal approach: the case of John the music talent - Blum, Carla Luciane (Debates em Educação, 2022)
This article aims to present an analysis of the journey carried out by John, a talented 70-year-old musician, divorced, when he underwent the 36 sessions of transpersonal therapy from April to July 2022, in a virtual way. The symptoms reported by John form anguish, loneliness, lack of self esteem and lack of hope for the future. Listening and regression resources, as well as meitation and music therapy were used. The focus of the sessions was given to work with conscious affectivity. Transpersonal therapy allowed John to meet the transdisciplinary state of consciousness with his own essence. This experience made it possible to raise self-esteem, giving him the possibility to achieve new goals, dazzle ways of thinking, feeling and acting, transforming him into the author of his own story. By strengthening his self-image, John expanded his creative and transformative process as he returned to composing music and opened himself up to a new love relationship, thus demonstrating personal and spiritual evolution.